Positive selection on sociobiological traits in invasive fire ants. Issue 15 (11th July 2018) - Privman, Eyal; Cohen, Pnina; Cohanim, Amir B.; Riba‐Grognuz, Oksana; Shoemaker, DeWayne; Keller, Laurent
Abstract: The fire ant Solenopsis invicta and its close relatives are highly invasive. Enhanced social cooperation may facilitate invasiveness in these and other invasive ant species. We investigated whether invasiveness in Solenopsis fire ants was accompanied by positive selection on sociobiological traits by applying a phylogenomics approach to infer ancient selection, and a population genomics approach to infer recent and ongoing selection in both native and introduced S. invicta populations. A combination of whole‐genome sequencing of 40 haploid males and reduced‐representation genomic sequencing of 112 diploid workers identified 1, 758, 116 and 169, 682 polymorphic markers, respectively. The resulting high‐resolution maps of genomic polymorphism provide high inference power to test for positive selection. Our analyses provide evidence of positive selection on putative ion channel genes, which are implicated in neurological functions, and on vitellogenin, which is a key regulator of development and caste determination. Furthermore, molecular functions implicated in pheromonal signalling have experienced recent positive selection. Genes with signatures of positive selection were significantly more often those overexpressed in workers compared with queens and males, suggesting that worker traits are under stronger selection than queen and male traits. These results provide insights into selection pressures and ongoing adaptation in an invasive social insect and support the hypothesis that sociobiological traits are under more positive selection than nonsocial traits in such invasive species.